Eksperimen Pemanfaatan Teknologi dalam Pembelajaran Fiqih di SMP-IT Al-Jabar Karawang - Muhammad Nasa’i Dwi Saputra; Lusiani Lestiana Indah; Muhammad Arifin Ilham; Filza Putri Amaliyah; Salma Sholeha AM (STIKes Ibnu Sina Ajibarang, 2025)
SMP-IT Al-Jabar Karawang is an Islamic private educational institution that combines the Qur'an memorization program with the Merdeka Curriculum approach and an all-day school system. This school aims to produce a superior Qur'anic generation, with modern management and adequate facilities. This study aims to assess how effective the Islamic Religious Education (PAI) teaching model in the digital era is in improving student learning outcomes. The methodology used was a quasi-experiment with a pre-test and post-test design involving two groups: a control group and an experimental group. All groups had two meetings before the final assessment using a post-test. The results showed the average N-Gain value of the control class as 0.5 (low category), but for the experimental class it could reach 0.65 (medium category). This shows that the application of digital-based PAI learning models is more successful in improving student learning outcomes than traditional methods. Therefore, digital-based learning models can be the way that is appropriate and can adapt to incorporating Islamic values into education in this modern era.